Strategic Tax Competition; Implications of National Ownership - Trond Olsen; Petter Osmundsen (Center for Economic Studies and ifo Institute (CESifo), 2000)
Two jurisdictions compete to capture the rents of a large multinational enterprise (MNE) which invests locally and which is partly owned by local investors. The MNE contributes to local welfare by tax payments and dividends, and it has private information about the efficiency of the operations in the two localisations. It is shown that the distortions in the MNE's real investment portfolio are determined by a trade-off between fiscal externalities and equity externalities, and that investments in the case of strategic tax competition may be lower than in the co-operative case. Ownership matters, and we show how the firm may reduce its overall tax payments by influencing the distribution of owner shares between investors in the two countries.
Keywords: 330; Tax competition; mobility; common agency